Clonal dominance and progression in Abelson murine leukemia virus lymphomagenesis. - Green, P L (1987)
We examined the clonality of tumors induced by an acutely transforming retrovirus which carries a single oncogene. Contrary to our expectation, tumors induced by the Abelson murine leukemia virus (A-MuLV) showed one to four major proviral integration events. To further investigate the process by which clonality was established, we analyzed the number of cells infected and transformed by A-MuLV at various times after in vivo infection. At the midpoint of tumor latency (14 days postinfection), we found that infection of total bone marrow cells by A-MuLV was efficient and polyclonal. However, only a minority of these infected cells were transformed as assayed in cell culture, and clonal dominance had already been established in this transformed cell population. Examination of the in vitro growth properties of transformed cells recovered from preleukemic and leukemic mice indicated that preleukemic cells had lower cloning efficiencies than primary tumor cells. Our results suggest that the rate-limiting step in this system of lymphomagenesis is the initial transformation of bone marrow target cells and that these cells undergo subsequent changes in cloning ability during the course of the disease that lead to an autonomous neoplastic state.